Net Profit Margin, Pertumbuhan Perusahaan dan Volatilitas Harga Saham Pada Perusahaan di Indonesia - Debbi Chyntia Ovami; Galih Supraja; Ari Irawan; Rustam Efendi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to examine and analyze the factors that influence stock price volatility in sub-construction and building companies listed on the Indonesia Stock Exchange in 2015-2020. Determination of the sample using the purposive sampling method, the sample obtained was 9 sub-construction and building companies in the 2015-2020 period in order to obtain 54 observational data. The data used are secondary data and the analysis technique used is multiple linear regression method by conducting a series of assumption tests to ensure the feasibility of the data. The data processing used in this study uses panel data regression with the help of Eviews 10 software. The results of this study find that Net Profit Margin (NPM) partially has a positive and significant effect on stock price volatility and Growth has a negative and insignificant effect on stock price volatility. Meanwhile, based on the results of the simultaneous test (F test) that all independent variables jointly significantly affect the dependent variable.